2020
DOI: 10.3390/vaccines8030482
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of COVID-19 Vaccination during the COVID-19 Pandemic in China

Abstract: Background: Faced with the coronavirus disease 2019 (COVID-19) pandemic, the development of COVID-19 vaccines has been progressing at an unprecedented rate. This study aimed to evaluate the acceptance of COVID-19 vaccination in China and give suggestions for vaccination strategies and immunization programs accordingly. Methods: In March 2020, an anonymous cross-sectional survey was conducted online among Chinese adults. The questionnaire collected socio-demographic characteristics, risk perception, the impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

136
943
55
30

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 850 publications
(1,164 citation statements)
references
References 32 publications
136
943
55
30
Order By: Relevance
“…First, in East and South East Asia, the overall acceptance rates among the general public were relatively high. This includes more than 90% acceptance rates in Indonesia, Malaysia and one study from China [32,33,40].…”
Section: Discussionmentioning
confidence: 99%
“…First, in East and South East Asia, the overall acceptance rates among the general public were relatively high. This includes more than 90% acceptance rates in Indonesia, Malaysia and one study from China [32,33,40].…”
Section: Discussionmentioning
confidence: 99%
“…Regionally, acceptance ranged from 38% in the Northeast to 49% in the West [28]. Internationally, some Asian countries had higher acceptance: 88.6-91.3% in China and 79.8% in South Korea-both also reported higher trust in central governments [21,29]. Other highly receptive countries included Brazil (85.36%), South Africa (81.58%), Denmark (80%), and the UK (79%); Russia had the lowest (54.9%), followed by France (58.9-62%), which also reported the largest rate of "unsure" responses (28%) [21,22].…”
Section: Trends In Vaccine Acceptance Hesitancy and Refusalmentioning
confidence: 99%
“…A top facilitator of confidence is doctors' recommendation [2,19,32,59], motivating 80% of Chinese [29] and 62% of Americans [13] (compared to 54% if the FDA endorsed the vaccine safety [56]). Opinion of families and friends also played a role [2].…”
Section: Vaccine Attributes and Individual Factorsmentioning
confidence: 99%
“…During the early stages of the pandemic (March-June), studies of small samples of European and Australian adults suggested that the majority of people surveyed reported that they would be vaccinated when a widely available vaccine was available [6][7] . Similarly, a nationally representative study of adults in China conducted in March found that 9 out of 10 would accept a vaccine when available 8 . US studies conducted early in the pandemic found that between 58% and 86% of adults reported they were likely to be vaccinated against COVID-19 6,[9][10][11] .…”
Section: Introductionmentioning
confidence: 99%